(untitled) (AYUSHDHARA, 2024)
The fundamentals of a healthy lifestyle, according to Ayurveda include following a regular schedule for Ahara-Vihar and Aachar depending on Hetu (material cause), Kala (season) and Desha (habitat). Poor hygiene and inconsistent eating habits are brought on by such a lifestyle. All these elements disrupt Dinacharya’s natural balance and contribute to frequent skin issues. Ayurveda has mentioned two types of treatment in skin disorders, Antahparimarjan and Bahirparimarjan which means respectively systemic and local therapy. One such Malahar used in skin disorders/skin cracks is Madhucchista and Jatyadi taila malahar. It is a classical formulation mentioned in Rasatarangini. The main ingredients are Madhucchista and Jatyadi Taila. This formulation is mentioned in eleventh Taranga of Rasatarangini. The drug Madhucchista has long been used as a ground component of ointments, and this practise is still prevalent today because moisturisers currently on the market still contain the ingredient. The medicine for external application as well as the base in numerous formulations has been described by Charaka, Sushruta, and Vagbhata, who have also referenced it in the treatment of Vatarakta, Vrana, Kushtha, and Vipadika. In the Bhasmaka Chikitsa, Charaka employed it internally. Jatyadi Taila being an Ayurvedic oil is used for wound healing in fissures, piles, and fistula. It speeds up the wound healing processes and results in quick recovery from these diseases. Local application of Jatyadi Taila helps in quick healing of fissures. It reduces pain, heals the cracks. This Malahar base helps in healing the skin by its Vrana Ropaka, Dashahara, Komalata property, reducing pain and swelling and thus, prevents further cracking. Cosmetically, it softens the skin and prevents from further roughening and cracking. So, it renders both therapeutic efficacy and cosmetic property.